2020
DOI: 10.1002/dta.2970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of theophylline and theobromine on exercise performance and implications for competition sport: A systematic review

Abstract: A systematic review was undertaken to evaluate studies on the effects of theophylline and theobromine on exercise performance in normal (healthy) subjects. Theophylline was found to have been studied on eight occasions and theobromine on one, the number of subjects per study ranging from seven to 15. In two exercise investigations, theophylline was superior to placebo at a p < 0.05 level and no different in four including one that was conducted in artificial hypoxia. In a treadmill time trial over 3 km, theobr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In the present study, the theophylline content and xanthine dehydrogenase gene expression in the caffeine metabolic pathway significantly changed. Theophylline and xanthine exert stimulant and bronchiectasis-promoting effects on humans (Kennedy, 2021), but their effects on aquatic animals are unclear. Therefore, their significance after M. bicuspidata infection requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the theophylline content and xanthine dehydrogenase gene expression in the caffeine metabolic pathway significantly changed. Theophylline and xanthine exert stimulant and bronchiectasis-promoting effects on humans (Kennedy, 2021), but their effects on aquatic animals are unclear. Therefore, their significance after M. bicuspidata infection requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of quinine were found in soccer players. It inhibits nerve stimulation by decreasing the excitability of the motor end plate and increasing the refractory period of skeletal muscular contraction [ 59 , 60 ].…”
Section: Mybpc3 Snp-associated Metabolitesmentioning
confidence: 99%
“…Theophylline is known to relax the smooth muscles in the bronchial airways and pulmonary blood vessels. It reduces pulmonary artery pressures and pulmonary vascular resistance, in addition to increasing both right and left ventricular ejection fractions [ 59 ]. This metabolite exerts these effects through different mechanisms.…”
Section: Mybpc3 Snp-associated Metabolitesmentioning
confidence: 99%
“…Fatigue occurs because of the role of lactic acid and can be defined as a decrease in muscle strength and power, causing disturbances during training and competition [11]. Many athletes, therefore, consume ergogenic substances or substances to increase productivity and control energy [9] One of the ergogenic substances that can be used is caffeine and theobromine [12].…”
Section: Introductionmentioning
confidence: 99%
“…Only one study was found regarding theobromine administration based on investigations in several works of literature. This leads the author to argue that studies on giving theobromine to physical activity are still very limited [12] Based on the description above, it has been explained that fatigue is the inability of muscles to perform physical activity. Therefore, substances are needed to reduce lactic acid levels.…”
Section: Introductionmentioning
confidence: 99%